Results of Displaced Lisfranc Injuries with Open Reduction and Fixation with K-Wires - Shrestha, Dinesh Kumar; Dhungel, Binayak; Lakhanpal, V. P.; Mishra, S. M. (Journal of Nepalgunj Medical College, 2017)
Background: The Lisfranc injury is an injury of the foot in which one or more metatarsal bones are displaced from the tarsal bones. Due to their low incidence and complexity, these injuries are often missed on initial evaluation. Prompt recognition and then anatomic reduction and stabilization gives best outcomes post treatment. Aim: The study aimed to compare short-term treatment results for tarso-metatarsal joint injuries with treatment outcomes and compare it with type of injury per classification. Methods: This was a prospective observational, analytical hospital based study. The subjects included in the study were classified according to radiological findings and treated with open reduction and K-wire fixation. Study subjects were immobilized for six weeks. Weight bearing was progressed slowly. Short term result was calculated by American orthopaedic foot and ankle society score (AOFAS) at six months. Results: Of the nine cases included in the study, low energy fall, five (55.55%) was commoner cause for injury followed by high energy road traffic accident (RTA) in four (44.44%) patients. Six fractures (66.67%) were of type A while, three (33.3%) were type B. Average day from injury to surgery was 3.11 (range 2-5). AOFAS Score calculated in six months average was 82.44(SD±12.79). In patients with type A injury mean AOFAS score was 89(SD±2.6), while in patients with type B injury had mean of 69.33(SD±15.82). The AOFAS score difference for the group A and B was statistically significant (P<0.05). Conclusions: Lisfranc injuries are life changing injuries as scores of AOFAS get lower even after 6 months of injury. Patients with type B injuries have poorer outcome than type A injuries. JNGMC Vol. 13 No. 2 December 2015, Page: 35-37